MODERN METHODS FOR EVALUATING THE CREDITWORTHINESS OF BANK’S BORROWERS-LEGAL ENTITIES OF UKRAINE - BALYTSKA, Mariia; PARZHYTSKA, Marharyta (Herald of Khmelnytskyi National University. Economic sciences, 2022)
At the present stage of development of financial and economic relations, lending is one of the most popular sources of covering the lack of financial resources necessary, in particular, to start the activity of an economic entity, expand production, eliminate the liquidity gap, etc. At the same time, enterprises operate in a changing environment, under the influence of permanent, as well as unpredictable risks and threats. Thus, intending to get a loan from a bank, a legal entity cannot always guarantee their timely return in full. In a crisis, legal entities often have significant losses, and therefore take loans to pay current liabilities. When providing loans to economic entities, banking institutions must be sure of their return. For this purpose, the creditworthiness of the borrower-legal entity is assessed, which ensures minimization of the risk of non-repayment of the bank's loan funds.The article discusses modern models for assessing the creditworthiness of a borrower, as well as their characteristics and advantages and disadvantages. Taking into account the theoretical and methodological aspects of assessing the creditworthiness of borrowers makes it possible to reasonably propose ways to improve them so that banks can further minimize credit risk in their activities, and the banking system remains financially stable. The study of existing methods for assessing the creditworthiness of a borrower-legal entity led to the conclusion that in order to obtain accurate and objective assessments of the creditworthiness of an enterprise, complex methods should be used. At the same time, the methodological support for assessing the creditworthiness of a borrower-legal entity, used by domestic banking institutions, requires further improvement in terms of developing tools for assessing the qualitative characteristics of an enterprise's creditworthiness. The article discusses the latest approaches to the methodology for assessing the creditworthiness of legal entities, such as credit rating, innovative credit scoring, including those based on the use of alternative data, based on the effective use of modern digital technologies: BigData, artificial intelligence, machine learning.
Keywords: creditworthiness; credit assessment methods; borrower-legal entity; indicators of financial condition